2022
DOI: 10.1002/cam4.5032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ferroptosis‐related molecular model and immune subtypes of hepatocellular carcinoma for individual therapy

Abstract: Background Excessive iron accumulation and lipid peroxidation are primary characteristics of ferroptosis in hepatocellular carcinoma (HCC). Ferroptosis inducer combined with immunotherapy has become a new hope for HCC patients. Therefore, the construction and validation of subtype‐specific sensitivity to ferroptosis inducer will be helpful for hierarchical management and precise individual therapy. Methods RNA‐seq transcriptome and clinical data of HCC patients were extracted from International Cancer Genome C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…SAT1 (spermidine/spermine-N1acetyltransferase 1) was chosen as a protective factor to construct a ferroptosis-relevant prediction model in HCC patients (Wang et al, 2021). Further research demonstrated that the expression of SAT1 was repressed in HCC tumor tissues compared with normal liver tissues (Long et al, 2023), which was also demonstrated in our validation test. The tumor-suppressor protein, p53, was discovered to have the ability to induce ferroptosis and inhibit tumor growth through facilitating SAT1 expression (Liu et al, 2020b).…”
Section: Discussionsupporting
confidence: 52%
“…SAT1 (spermidine/spermine-N1acetyltransferase 1) was chosen as a protective factor to construct a ferroptosis-relevant prediction model in HCC patients (Wang et al, 2021). Further research demonstrated that the expression of SAT1 was repressed in HCC tumor tissues compared with normal liver tissues (Long et al, 2023), which was also demonstrated in our validation test. The tumor-suppressor protein, p53, was discovered to have the ability to induce ferroptosis and inhibit tumor growth through facilitating SAT1 expression (Liu et al, 2020b).…”
Section: Discussionsupporting
confidence: 52%
“…We have observed that several previous studies had focused on the identification of ferroptosis-related genes signature in HCC, including signature of five ferroptosis-related genes constructed by Zhang et al (2022) , the signature of four ferroptosis-related genes constructed by Long et al (2022) , the signature of five ferroptosis-related genes constructed by Wan et al (2022) , and the signature of seven ferroptosis-related genes constructed by Wang et al (2022) . It is worth mentioning that these signature have their own advantages.…”
Section: Discussionmentioning
confidence: 99%
“…We compared our own model to 12 other published HCC prognostic models to better show its predictive power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Multivariate analysis was used to calculate the risk value and prognostic evaluation for each dataset, leveling the playing field amongst the four models.…”
Section: New Model As a New Predictor Of Hccmentioning
confidence: 99%